A bio-based, facile approach for the preparation of covalently functionalized carbon nanotubes aqueous suspensions and their potential as heat transfer fluids - Sadri, R.; Hosseini, M.; Kazi, S.N.; Bagheri, S.; Zubir, M.N.M.; Solangi, K.H.; Zaharinie, T.; Badarudin, A. (Elsevier, 2017)
In this study, we propose an innovative, bio-based, environmentally friendly approach for the covalent functionalization of multi-walled carbon nanotubes using clove buds. This approach is innovative because we do not use toxic and hazardous acids which are typically used in common carbon nanomaterial functionalization procedures. The MWCNTs are functionalized in one pot using a free radical grafting reaction. The clove-functionalized MWCNTs (CMWCNTs) are then dispersed in distilled water (DI water), producing a highly stable CMWCNT aqueous suspension. The CMWCNTs are characterized using Raman spectroscopy, X-ray photoelectron spectroscopy and transmission electron microscopy. The electrostatic interactions between the CMWCNT colloidal particles in DI water are verified via zeta potential measurements. UV–vis spectroscopy is also used to examine the stability of the CMWCNTs in the base fluid. The thermo-physical properties of the CMWCNT nano-fluids are examined experimentally and indeed, this nano-fluid shows remarkably improved thermo-physical properties, indicating its superb potential for various thermal applications.